Modeling the Implications Green Retrofitting River Conservation was Validated using (SEM) Analysis - Arif, Eka Juni; Sinaga, Lastarida; Kristiyanto, Kristiyanto; Barri, Ahmad; Ator, Wyllem Thomas (Universitas Ibn Khaldun Bogor, 2024)
According to the 2015 United Nations Framework Convention on Climate Change (UNFCCC), reducing CO2 in the atmosphere is essential to reduce related environmental problems, considering the increasing demand for air due to climate change. Carbon capture and sequestration is an attractive method for reducing carbon dioxide (CO2) emissions from the atmosphere. However, in some places, agricultural landscapes face problems due to air resources. Trees play a very important role in the fight against climate change. They pollute the air, stop landslides, absorb CO2 and some air pollutants, and absorb phosphate and nitrate runoff. Ten main elements, ordered from least to most important, were identified using research techniques that combine SEM-PLS to process survey data and find the most influential components. River conservation verification in Envision has the greatest impact. According to this research, the following things influence the implementation of green retrofits on green rivers: energy savings; emission reduction; use of the latest energy; the existence of an environmentally friendly green river program; cost planning and design; project feasibility studies; material costs; and use of the latest technology. It is hoped that the results of this research will increase public awareness and concern regarding the implementation of environmentally friendly green rivers as an effort to make rivers greener and more natural, reduce operational costs, and provide comfort for the community.